Comparation of two boron extractant solutions and determination of its content in soil and banana plant. - Obando Bustos, Veda (2018)
The objective of the study was to compare 2 boron extracting solutions (calcium phosphate and Mehlich 3), as well as to determine its content in soil and banana plant (third leaf). The study was carried out in the Chemical Laboratory of CORBANA SA, located in the province of Limón, Pococí county, La Rita district, in 2015. For this purpose, soil samples and leaf tissue were collected from banana plantations located in the Caribbean of Costa Rica. Soils with boron concentration lower than 0.2 mg.l-1 had a greater extraction of the element with the Mehlich 3 solution, in comparison with the calcium phosphate solution. Content between 0.2 and 0.7 mg.l-1 showed, on the other hand, a correlation of 68% between both solutions. Concentrations higher than 2 mg.l-1 exhibited a correlation of 98%. Ninety percent of analyzed soil samples had boron concentrations of less than 1.0 mg.l-1, with the most samples (64%) at contents of 0.2 to 0.7 mg.l-1. Recommended boron concentration for banana plants should range between 0.1 to 1.0 mg.l-1, so most sampled soils presented adequate values. Foliar boron contents were 10 to 15 mg.kg-1 in the inner central section of the third leaf, while in the outer section of the leaf (border) they were 10 to 70 mg.kg-1 with an increase in its concentration towards the edge of the leaf. Results indicate the advantage of using the Mehlich 3 over the calcium phosphate solution for the determination of boron in soil samples.